Exosomes Derived from the Human Primary Colorectal Cancer Cell Line SW480 Orchestrate Fibroblast‐Led Cancer Invasion. Issue 14 (20th July 2020) - Rai, Alin; Greening, David W.; Xu, Rong; Suwakulsiri, Wittaya; Simpson, Richard J.
Abstract: In localized tumors, basement membrane (BM) prevents invasive outgrowth of tumor cells into surrounding tissues. When carcinomas become invasive, cancer cells either degrade BM or reprogram stromal fibroblasts to breach BM barrier and lead invasion of cancer cells into surrounding tissues in a process called fibroblast‐led invasion. However, tumor‐derived factors orchestrating fibroblast‐led invasion remain poorly understood. Here it is shown that although early‐stage primary colorectal adenocarcinoma (SW480) cells are themselves unable to invade Matrigel matrix, they secrete exosomes that reprogram normal fibroblasts to acquire de novo capacity to invade matrix and lead invasion of SW480 cells. Strikingly, cancer cells follow leading fibroblasts as collective epithelial‐clusters, thereby circumventing need for epithelial to mesenchymal transition, a key event associated with invasion. Moreover, acquisition of pro‐invasive phenotype by fibroblasts treated with SW480‐derived exosomes relied on exosome‐mediated MAPK pathway activation. Mass spectrometry‐based protein profiling reveals that cancer exosomes upregulate fibroblasts proteins implicated in focal adhesion (ITGA2/A6/AV, ITGB1/B4/B5, EGFR, CRK), regulators of actin cytoskeleton (RAC1, ARF1, ARPC3, CYFIP1, NCKAP1, ICAM1, ERM complex), and signalling pathways (MAPK, Rap1, RAC1, Ras) important in pro‐invasive remodeling of extracellular matrix. Blocking tumor exosome‐mediated signaling to fibroblasts therefore represents an attractive therapeutic strategy in restraining tumors by perturbing stroma‐driven invasive outgrowth.